PENGARUH KUALITAS PELAYANAN KESEHATAN TERHADAP KEPUASAN PASIEN BPJS KESEHATAN DI PUSKESMAS PATUMBAK KABUPATEN DELI SERDANG TAHUN 2020 - VIKTOR EDYWARD MARBUN; EVALINA MANURUNG (Jurnal Inovasi Kesehatan Masyarakat, 2020)
Many human resources at public health center assume that the number of participants Social Health Care Assurance will burden or increase their workload so that the impact on the quality of health services in health centers. Similary, the assumption of the patient Social Health Care Assurance, because using Social Health Care Assurance card then the services that obtained feared can not be satisfactory. The purpose of this research is the analyze the effect of quality of health services on Social Health Care Assurance patient satisfactory. The research is quantitative research with survey method through explanatory research approach. The research was conducted at Patumbak Public Health Center Deli Serdang District. The Population of this research is 32.016 people and 90 people as sample. Data analysis use univariate analysis, bivariate analysis with chi-square and multivariate analysis use multiple logistic regression test at 95 confidence level (α=0,05)The results showed that the quality of health services significantly affected the satisfaction of BPJS Patients at Patumbak Community Health Center, P = 0,000. All dimensions of health service quality have an effect on patient satisfaction of BPJS at Patumbak Community Health Center that is direct evidence (tangibles, reliability (reliability), responsiveness, assurance and empathy. All confounding variables are sex, education occupation, membership of BPJS, distance of house to Health Center, none has an effect on patient satisfaction BPJS , with p > 0,05. The most dominant variable of the effect on patient satisfaction is the variable of Empathy, with the value of RP = 0,235 means that respondents stated that reliable health services will services. It is suggested to health workers at Patumbak Public Helath Center, Deli Serdang district regency to maintain good service quality and continuously improve service quality to patients by showing Empathy in work, hospitality to all patients, responding to problems complained of patients and empthy on patients.